Drug resistant TB: UK multicentre study (DRUMS): Treatment, management and outcomes in London and West Midlands 2008–2014. Issue 3 (March 2017) - Arnold, Amber; Cooke, Graham S.; Kon, Onn Min; Dedicoat, Martin; Lipman, Marc; Loyse, Angela; Butcher, Philip D.; Ster, Irina Chis; Harrison, Thomas Stephen
Summary: Objectives: Detailed information regarding treatment practices and outcomes of MDR-TB treatment in the UK is required as a baseline for care improvements. Methods: 100 consecutive cases between 2008 and 2014 were reviewed retrospectively at 4 MDR-TB treatment centres in England to obtain information on drug treatment choices, hospital admission duration and outcomes for MDR-TB. Results: Initial hospital admission was long, median 62.5 (IQR 20–106, n = 92) days, and 13% (12/92) of patients lost their home during this period. Prolonged admission was associated with pulmonary cases, cavities on chest radiograph, a public health policy of waiting for sputum culture conversion (CC) and loss of the patient's home. Sputum CC occurred at a median of 33.5 (IQR 16–55, n = 46) days. Treatment success was high (74%, 74/100) and mortality low (1%, 1/100). A significant proportion of the cohort had "neutral" results due to deportation and transfer overseas (12%, (12/100)). 14% (14/100) had negative outcomes for which poor adherence was the main reason (62%, 9/14). Conclusions: Successful outcome is common in recognised centres and limited by adherence rather than microbiological failure. Duration of hospital admission is influenced by lack of suitable housing and some variation in public health practice. Wider access to long-term assisted living facilities could improve completion rates. Highlights: Treatment practices and outcomes for MDR-TB treatment in the UK are described. Treatment success is high limited by adherence rather than microbiological failure. Variations in public health practice and housing lead to long hospital admissions. New models and infrastructure are required to reduce poor adherence. New methods using whole genome sequencing are required to shorten hospitalisation.